The Relationship Between Pain and Eating among Overweight and Obese Individuals with Osteoarthritis: An Ecological Momentary Study - Karmel W Choi; Tamara J Somers; Michael A Babyak; Kathleen J Sikkema; James A Blumenthal; Francis J Keefe (Pain Research and Management)
BACKGROUND: Osteoarthritis (OA) patients who are overweight or obese report higher levels of pain compared with their normal-weight OA counterparts. Evidence suggests that overweight or obese OA patients also experience pain relief from eating foods high in calories, fat or sugar. Eating to alleviate pain may be problematic because it can lead to additional weight gain, which may contribute to heightened pain.